2011
DOI: 10.1016/j.cub.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The Requirement for the Dam1 Complex Is Dependent upon the Number of Kinetochore Proteins and Microtubules

Abstract: Summary The Dam1 complex attaches the kinetochore to spindle microtubules and is a processivity factor in vitro [1, 2]. In Saccharomyces cerevisiae, which has point centromeres that attach to a single microtubule, deletion of any Dam1 complex member results in chromosome segregation failures and cell death [3–5]. In Schizosaccharomyces pombe, which has epigenetically-defined regional centromeres that each attach to 3–5 kinetochore microtubules, Dam1 complex homologs are not essential [6]. To ask why the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 35 publications
(49 reference statements)
3
67
0
Order By: Relevance
“…The reason for this unusual pattern of centromeric chromatin seen in vivo is still unknown, but it may be attributable to replacement of histone H3 by CENP-A. CENP-A molecules have been shown to replace histone H3 molecules either partially or fully in centromeric chromatin in different fungi (17,80,110,123). Studies in S. pombe have suggested that the unusual smeary pattern of partial MNase digestion could be due to protection provided by an intact kinetochore.…”
Section: Cenp-a: the Universal Component Of Centromeric Chromatinmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this unusual pattern of centromeric chromatin seen in vivo is still unknown, but it may be attributable to replacement of histone H3 by CENP-A. CENP-A molecules have been shown to replace histone H3 molecules either partially or fully in centromeric chromatin in different fungi (17,80,110,123). Studies in S. pombe have suggested that the unusual smeary pattern of partial MNase digestion could be due to protection provided by an intact kinetochore.…”
Section: Cenp-a: the Universal Component Of Centromeric Chromatinmentioning
confidence: 99%
“…In S. cerevisiae, CENP-A/Cse4 proteolysis, which is mediated by Psh1, an E3 ubiquitin ligase, restricts its localization primarily to the centromere (30,56,102). Overexpression of CENP-A/CaCse4 results in recruitment of more CENP-A/CaCse4 molecules along with other kinetochore proteins such as Mtw1 at the centromere in C. albicans (17,106). Posttranslational modifications associated with the N-terminal histone tail are related to different functional states of chromatin-like repression (silencing) or activation of transcription.…”
Section: Cenp-a: the Universal Component Of Centromeric Chromatinmentioning
confidence: 99%
“…microtubule: 1 kinetochore. This is the case in S. cerevisiae (Cheeseman et al, 2001;Janke, Ortiz, Tanaka, Lechner, & Schiebel, 2002;Li, Li, & Elledge, 2005) and C. albicans (Burrack, Applen, & Berman, 2011;Thakur & Sanyal, 2011), but not so for S. pombe (Sanchez-Perez et al, 2005). This difference has been postulated to reflect the more stringent requirement for maintaining connection with the depolymerizing microtubule when a single point of attachment is present; thus, under these circumstances, the ring may provide necessary stability (Burrack et al, 2011;Thakur & Sanyal, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…This is the case in S. cerevisiae (Cheeseman et al, 2001;Janke, Ortiz, Tanaka, Lechner, & Schiebel, 2002;Li, Li, & Elledge, 2005) and C. albicans (Burrack, Applen, & Berman, 2011;Thakur & Sanyal, 2011), but not so for S. pombe (Sanchez-Perez et al, 2005). This difference has been postulated to reflect the more stringent requirement for maintaining connection with the depolymerizing microtubule when a single point of attachment is present; thus, under these circumstances, the ring may provide necessary stability (Burrack et al, 2011;Thakur & Sanyal, 2011). Outside of the yeasts, sequence-based homologues of the Dam1 complex proteins are not identifiable, though a variety of evidence suggests that the functional homologue in metazoans may be the Ska complex (Gaitanos et al, 2009;Guimaraes & Deluca, 2009;Hanisch, Sillje, & Nigg, 2006;Jeyaprakash et al, 2012;Welburn et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The DASH complex is conserved in other fungi but not in metazoa. The requirement for DASH is related to the number of microtubule-binding sites per kinetochore (Burrack et al, 2011;Thakur and Sanyal, 2011). Although the DASH complex is essential for viability in budding yeast, where kinetochores bind to a single microtubule, it is not required for viability in fission yeast, where kinetochores bind to between two and four microtubules (Liu et al, 2005;Sanchez-Perez et al, 2005).…”
Section: Introductionmentioning
confidence: 99%